ANALISIS PENERAPAN AKUNTANSI MANAJEMEN LINGKUNGAN PADA UD. SANTOSO DI MANADO - Harimisa, Siti Rachmi; Nangoi, Grace B.; Runtu, Treesje (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Environmental management accounting is one of the sub-systems of environmental accounting explaining a number of issues regarding the problem of quantifying the business impacts of a company into a number of monetary units. This study aims to determine the application of environmental management accounting at UD. Santoso in Manado. The method of analysis used in this thesis research is a comparative descriptive method that is by comparing the application of management accounting methods in general with the application of corporate management accounting. The results obtained, UD. Santoso has not applied the environmental management accounting as much as possible because there is still material, water and energy wasted in some production processes which indirectly increase production cost.Keywords: analysis, aml, cost